Clarification of serotonin‐induced effects in peripheral artery disease observed through the femoral artery response in models of diabetes and vascular occlusion: The role of calcium ions. (July 2017) - Stojanović, Marko; Prostran, Milica; Janković, Radmila; Radenković, Miroslav
Summary: Recent findings have demonstrated that serotonin is an important participant in the development and progression of peripheral artery diseases. Taking this into consideration, the goals of this study were to investigate the effects of serotonin on isolated Wistar rat femoral arteries in both healthy and diabetic animals, with and without artery occlusion, with a particular focus on determining the role of calcium in this process. Contraction experiments with serotonin on intact and denuded femoral artery rings, in the presence or absence of nifedipine and ouabain (both separately, or in combination), as well as Ca 2+ ‐free Krebs‐Ringer bicarbonate solution were performed. The serotonin‐induced results were concentration dependent, but only in healthy animals. The endothelium‐dependent contraction of the femoral artery was assessed. In healthy animals, the endothelium‐reliant part of contraction was dependent on the extracellular calcium, while the smooth muscle‐related part was instead dependent on the intracellular calcium. In diabetic animals, both nifedipine and ouabain influenced serotonin‐induced vascular effects by blocking intracellular calcium pathways. However, this was diminished after the simultaneous administration of both blockers.